Acoustic emission feature events during rock failure and their cumulative probability distribution: Case study of phosphate rock and granite - Zhang, Yi; Feng, Guangliang; Lin, Manqing; Li, Xianfu; Gao, Chengcheng; Liang, Xiaoshuai (Frontiers in Environmental Science, 2022)
Rock mass failure is gradually becoming more common as the number of geotechnical engineering projects continues to increase. In this paper, the probability density distributions of initial and peak frequency events in the acoustic emission (AE) from two types of rock (phosphate rock and granite) undergoing failure are analyzed. Feature events (FEs) in this AE are proposed and obtained. The probabilities of events with an initial frequency of 1,000 kHz and peak frequency of 625 kHz are found to be higher than those with other frequencies. The evolutionary behavior of the cumulative probability distributions (CPDs) of the FEs as the rocks fail is subsequently investigated. The characteristic FEs of the AE and their CPD evolution behavior in the two rocks are then compared and contrasted. The CPD curves derived for both types of rock consist of four stages: slow rise – concave rise – rapid rise – slow rise. The differences related to the FEs for the two rocks are also found. The duration of the last stage (near rock failure) is quite different for phosphate rock and granite. The peak frequencies of the FEs are the highest and the smallest in the two rocks, respectively. Our method of analyzing the AE data and results provide a theoretical method for analyzing the stability of rock masses and predicting their failure.